Activatable NIR-II photoacoustic imaging and photochemical synergistic therapy of MRSA infections using miniature Au/Ag nanorods. (August 2020) - Mei, Zihan; Gao, Duyang; Hu, Dehong; Zhou, Huichao; Ma, Teng; Huang, Liang; Liu, Xin; Zheng, Rongqin; Zheng, Hairong; Zhao, Ping; Zhou, Jianqiao; Sheng, Zonghai
Abstract: Multidrug-resistant Staphylococcus aureus (MRSA) seriously endanger human health. The development of efficient methods to eliminate the infections and monitor the treatment process are of great significance. Near-infrared-II (NIR-II) photoacoustic (PA) imaging and photothermal therapy (PTT) are highly integrated theranostic platforms with superior performance including a low imaging background, increased tissue penetration depth, and high photothermal threshold. Herein, we report an activatable near-infrared II (NIR-II) phototheranostic strategy using miniature Au/Ag nanorods (NRs) for the photochemical synergistic therapy of MRSA infections and in situ monitoring of the treatment progress. Au/Ag NRs were efficiently activated by ferricyanide solution and allowed to continuously release free Ag + to eliminate MRSA, triggering NIR-II photothermal and PA performance enhancement. The activated NIR-II photothermal effect in turn accelerated the release of free Ag + from Au/Ag NRs for the synergistic elimination of gram-positive Staphylococcus aureus and promoted wound healing. No photothermal damages or free Ag + -induced side effects were observed in treated mice. After synergistic treatment, a 20-fold NIR-II PA signal increase with a maximum signal-to-noise measurement of 9.5 was observed between the implanted site and normal tissue, enabling sensitive monitoring of Ag + release process. The prepared Au/Ag NRs were stable and biocompatible, showing great potential for activatable NIR-II phototheranostic application.